PENGARUH PEMBERIAN BERBAGAI JENIS PAKAN TERHADAP PERTUMBUHAN LOBSTER AIR TAWAR - Taufiq, Mohammad; Dewi, Kurnia Maya Candra; Handono, Handono; Rosidi, Irsad (Universitas Nahdatul Ulama Surabaya, 2016)
Lobster breeding is a business to make as much profit as possible using advanced technology. The objective of the research is to find out the effect of feeding pellet, blood worms, mixed (blood worms and pellets) on the growth of crayfish (Cherax quadricarinatus), so by applying the type of these feed, they are able to support the growth of crayfish (Cherax quadricarinatus) optimally, This study is experimental research and uses a Randomized Completely Block Design with one treatment that is using feed ing for crayfish which consists of pellets, blood worms, and mixed feed (pellets and blood worms) in 3 repetitions. Research finding indicates that the type of feed which support growth lobster is a mixture of feed (pellets and blood worms). This is due to the protein contents of blood worm which are enriched by pellets nutritious and fulfilling need of lobster. On the feed mixture shows optimal qualifying that appropriate with the living conditions of crayfish, that is DO concentration of 4.47 ppm, pH 7.81, and the the temperature of 27  C.